Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 68083 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Sciurus carolinensis Gmelin, 1788" ] } The dataset includes 68083 records from 157 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0008430-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences